The Synthesis, Crystal Structure, Modification, and Cytotoxic Activity of α-Hydroxy-Alkylphosphonates - Zsuzsanna Szalai; Anna Sára Kis; Angéla Takács; László Kőhidai; Konstantin Karaghiosoff; Mátyás Czugler; László Drahos; György Keglevich (Molecules)
A series of α-hydroxy-alkylphosphonates and α-hydroxy-alkylphosphine oxides were synthesized by the Pudovik reaction of acetaldehyde and acetone with dialkyl phosphites or diarylphosphine oxides. The additions were performed in three different ways: in liquid phase using triethylamine as the catalyst (1), on the surface of Al2O3/KF solid catalyst (2), or by a MW-assisted Na2CO3-catalyzed procedure (3). In most of the cases, our methods were more efficient and more robust than those applied in the literature. Two of the α-hydroxy-alkylphosphonates were subjected to single-crystal X-ray analysis, suggesting a dimeric and a chain supramolecular buildup in their respective crystals. Four α-hydroxy-alkylphosphonates and one α-hydroxy-ethylphosphine oxide were reacted with different acid chlorides to afford ten α-acyloxyphosphonates. Diethyl α-hydroxy-ethylphosphonate was transformed to the methanesulfonyloxy derivative that was useful in the Michaelis–Arbuzov reaction with triethyl phosphite and ethyl diphenylphosphinite to afford tetraethyl ethylidenebisphosphonate and diethyl α-(diphenylphosphinoyl)-ethylphosphonate, respectively. The α-hydroxyphosphonates and α-hydroxyphosphine oxides prepared were subjected to bioactivity studies, and the compounds tested exhibited limited cytotoxic effects on U266 cells with modest reductions in viability at a concentration of 100 μM.